Pre-Service Teachers’ Challenges in Managing Students’ Interaction and Students’ Participation Using the Zoom Application in Teaching English During Apprenticeship Practice - Roihatul Jannah; Natalia Anggrarini; Indra Yoga Prawiro (Universitas Sarjanawiyata Tamansiswa, 2022)
Various applications or online learning media are scattered during the Covid-19 pandemic. One of them is Zoom which is beneficial for communicating remotely; all teacher explanations can be conveyed clearly without having to meet physically. This study aims to discover the challenges in managing students’ interaction and the level of student participation by using the Zoom application in teaching English during the Covid-19 pandemic. This descriptive case study reported that the preservice teachers’ challenges in managing student-to-teacher interaction while learning English using the Zoom application were the lack of feedback given by students to the teacher, the lack of immediacy between students and teachers, and the internet connection. Meanwhile, in managing student-to-student interaction, the challenges are lack of interaction, motivation, and social presence. The student participation in learning English using zoom was at the level of inbound participants. The students use verbal or oral as their way to contribute and participate in online discussions. In addition, students also provide interesting questions and meaningful feedback so that the three indicators refer to the characteristics possessed by inbound participants. This study concludes that feedback and immediacy by teachers are consistently needed during online meetings. To build meaningful interaction among students, interaction, motivation, and social presence should be maintained. Students’ awareness of interaction, motivation, and social presence in online meetings is essential. Although teachers and students have online meetings, inbound participation is reflected. The students do their verbal and oral online as they do in offline meetings.